Effect of Roasting Method on Physico-Mechanical and Roasting Characteristics of Chickpea (Cicer arietinum) - Sharanagat, Vijay Singh; Jogihalli, Praveen; Singh, Lochan; Kumar, Kshitiz (Journal of Agricultural Engineering, 2018)
Chickpea grains were roasted by traditional sand roasting (180, 200 and 220ÂºC) and microwave roasting (450 W, 600 W and 900 W) for 5, 10 and 15 min. The effects of roasting method and their parameters on physico-mechanical and roasting characteristics were determined. Roasting led to an increase in size, sphericity, angle of repose, porosity and puffing index of chickpea. Significant (p